Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure, let's solve these equations one by one.
Equation 3:
[tex]$\frac{x}{6} + 5 = \frac{2}{3} + x$[/tex]
To solve this equation, follow these steps:
1. Get rid of the fractions by multiplying every term by the common denominator, which is 6 in this case:
[tex]$x + 30 = 4 + 6x$[/tex]
2. Rearrange the equation to gather all terms involving [tex]\(x\)[/tex] on one side:
[tex]$x - 6x = 4 - 30$[/tex]
[tex]$-5x = -26$[/tex]
3. Divide both sides by -5 to isolate [tex]\(x\)[/tex]:
[tex]$x = \frac{-26}{-5}$[/tex]
[tex]$x = 5.2$[/tex]
So, the solution for Equation 3 is:
[tex]$x = 5.2$[/tex]
Equation 4:
[tex]$\frac{2}{3x} + \frac{1}{2} = \frac{3}{2x} + \frac{13}{6}$[/tex]
To solve this equation, follow these steps:
1. Get rid of the fractions by multiplying every term by the common denominator, which is [tex]\(6x\)[/tex] in this case:
[tex]$6x \left( \frac{2}{3x} + \frac{1}{2} \right) = 6x \left( \frac{3}{2x} + \frac{13}{6} \right)$[/tex]
2. Simplify the equation:
[tex]$4 + 3x = 9 + 13x$[/tex]
3. Rearrange the equation to gather all terms involving [tex]\(x\)[/tex] on one side:
[tex]$4 + 3x - 9 = 13x$[/tex]
[tex]$-5 = 10x$[/tex]
4. Divide both sides by 10 to isolate [tex]\(x\)[/tex]:
[tex]$x = \frac{-5}{10}$[/tex]
[tex]$x = -0.5$[/tex]
So, the solution for Equation 4 is:
[tex]$x = -0.5$[/tex]
Equation 5:
[tex]$\frac{6 - 8x}{10} = \frac{8 - 6x}{8} - \frac{10 - 4x}{4}$[/tex]
To solve this equation, follow these steps:
1. Combine the fractions on the right-hand side to a single fraction:
[tex]$\frac{6 - 8x}{10} = \frac{8 - 6x}{8} - \frac{10 - 4x}{4}$[/tex]
2. Find the common denominator for the fractions on the right-hand side, which is 8:
[tex]$\frac{8 - 6x}{8} - \frac{20 - 8x}{8}$[/tex]
[tex]$\frac{8 - 6x - (20 - 8x)}{8}$[/tex]
[tex]$\frac{8 - 6x - 20 + 8x}{8}$[/tex]
[tex]$\frac{-12 + 2x}{8}$[/tex]
[tex]$\frac{2x - 12}{8}$[/tex]
3. Now set the left-hand side equal to the right-hand side:
[tex]$\frac{6 - 8x}{10} = \frac{2x - 12}{8}$[/tex]
4. Cross-multiply to get rid of the fractions:
[tex]$(6 - 8x) \cdot 8 = (2x - 12) \cdot 10$[/tex]
5. Simplify the equation:
[tex]$48 - 64x = 20x - 120$[/tex]
6. Rearrange the equation to gather all terms involving [tex]\(x\)[/tex] on one side:
[tex]$48 + 120 = 20x + 64x$[/tex]
[tex]$168 = 84x$[/tex]
7. Divide both sides by 84 to isolate [tex]\(x\)[/tex]:
[tex]$x = \frac{168}{84}$[/tex]
[tex]$x = 2$[/tex]
So, the solution for Equation 5 is:
[tex]$x = 2$[/tex]
Equation 3:
[tex]$\frac{x}{6} + 5 = \frac{2}{3} + x$[/tex]
To solve this equation, follow these steps:
1. Get rid of the fractions by multiplying every term by the common denominator, which is 6 in this case:
[tex]$x + 30 = 4 + 6x$[/tex]
2. Rearrange the equation to gather all terms involving [tex]\(x\)[/tex] on one side:
[tex]$x - 6x = 4 - 30$[/tex]
[tex]$-5x = -26$[/tex]
3. Divide both sides by -5 to isolate [tex]\(x\)[/tex]:
[tex]$x = \frac{-26}{-5}$[/tex]
[tex]$x = 5.2$[/tex]
So, the solution for Equation 3 is:
[tex]$x = 5.2$[/tex]
Equation 4:
[tex]$\frac{2}{3x} + \frac{1}{2} = \frac{3}{2x} + \frac{13}{6}$[/tex]
To solve this equation, follow these steps:
1. Get rid of the fractions by multiplying every term by the common denominator, which is [tex]\(6x\)[/tex] in this case:
[tex]$6x \left( \frac{2}{3x} + \frac{1}{2} \right) = 6x \left( \frac{3}{2x} + \frac{13}{6} \right)$[/tex]
2. Simplify the equation:
[tex]$4 + 3x = 9 + 13x$[/tex]
3. Rearrange the equation to gather all terms involving [tex]\(x\)[/tex] on one side:
[tex]$4 + 3x - 9 = 13x$[/tex]
[tex]$-5 = 10x$[/tex]
4. Divide both sides by 10 to isolate [tex]\(x\)[/tex]:
[tex]$x = \frac{-5}{10}$[/tex]
[tex]$x = -0.5$[/tex]
So, the solution for Equation 4 is:
[tex]$x = -0.5$[/tex]
Equation 5:
[tex]$\frac{6 - 8x}{10} = \frac{8 - 6x}{8} - \frac{10 - 4x}{4}$[/tex]
To solve this equation, follow these steps:
1. Combine the fractions on the right-hand side to a single fraction:
[tex]$\frac{6 - 8x}{10} = \frac{8 - 6x}{8} - \frac{10 - 4x}{4}$[/tex]
2. Find the common denominator for the fractions on the right-hand side, which is 8:
[tex]$\frac{8 - 6x}{8} - \frac{20 - 8x}{8}$[/tex]
[tex]$\frac{8 - 6x - (20 - 8x)}{8}$[/tex]
[tex]$\frac{8 - 6x - 20 + 8x}{8}$[/tex]
[tex]$\frac{-12 + 2x}{8}$[/tex]
[tex]$\frac{2x - 12}{8}$[/tex]
3. Now set the left-hand side equal to the right-hand side:
[tex]$\frac{6 - 8x}{10} = \frac{2x - 12}{8}$[/tex]
4. Cross-multiply to get rid of the fractions:
[tex]$(6 - 8x) \cdot 8 = (2x - 12) \cdot 10$[/tex]
5. Simplify the equation:
[tex]$48 - 64x = 20x - 120$[/tex]
6. Rearrange the equation to gather all terms involving [tex]\(x\)[/tex] on one side:
[tex]$48 + 120 = 20x + 64x$[/tex]
[tex]$168 = 84x$[/tex]
7. Divide both sides by 84 to isolate [tex]\(x\)[/tex]:
[tex]$x = \frac{168}{84}$[/tex]
[tex]$x = 2$[/tex]
So, the solution for Equation 5 is:
[tex]$x = 2$[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.